Sweet potato (Ipomoea batatas L.): Climate resilient crop for food security in arid and semi-arid regions - A review (Indian Journal of Arid Horticulture, 2025)
Sweet potato is a crucial crop for enhancing food security, particularly in arid and semi-arid regions where climate change and water scarcity pose significant challenges to agriculture. However, osmotic stress severely impacts its agronomic and economic productivity by triggering morphological, physiological and biochemical alterations. In response to drought, sweet potato activates various adaptive mechanisms, including growth regulation, antioxidant defense, osmolyte accumulation and stress protein synthesis. These physiological, metabolic, and genetic responses serve as essential indicators for selecting drought-tolerant genotypes. The primary goal of breeding programs in drought-prone regions is to develop high-yielding, drought-resistant varieties. Understanding the physiological and biochemical traits of drought-tolerant genotypes is critical for improving selection strategies. By integrating conventional breeding, molecular techniques, and biotechnological innovations, drought-resilient sweet potato varieties can be developed, making cultivation more sustainable and cost-effective for smallholder farmers. This review explores the effects of drought stress on sweet potato productivity, its adaptation strategies, crop management practices, and advanced breeding approaches to enhance drought tolerance.